2020
DOI: 10.1111/jcmm.15871
|View full text |Cite
|
Sign up to set email alerts
|

MFGE8 is down‐regulated in cardiac fibrosis and attenuates endothelial‐mesenchymal transition through Smad2/3‐Snail signalling pathway

Abstract: Heart failure (HF) is an end-stage manifestation of many cardiac diseases leading to severe functional impairment and cardiac insufficiency. The basic pathogenesis of heart failure is thought to be associated with ventricular remodelling, which is characterized by excessive cardiac fibrosis (CF). 1 Current studies indicate that myofibroblasts transformed from endothelial cells (ECs) through endothelial-mesenchymal transition (EndMT) process are responsible for cardiac fibrosis. 2,3 During EndMT, ECs experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…The results suggest that MFG-E8 has an antifibrotic property in the pancreas. This is consistent with the reported function of MFG-E8 in hepatic fibrosis, renal fibrosis and skin fibrosis (Fujiwara et al, 2019;Shi et al, 2020;Wang et al, 2020). Thus, MFG-E8 may be a promising option for the treatment of pancreatic fibrosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results suggest that MFG-E8 has an antifibrotic property in the pancreas. This is consistent with the reported function of MFG-E8 in hepatic fibrosis, renal fibrosis and skin fibrosis (Fujiwara et al, 2019;Shi et al, 2020;Wang et al, 2020). Thus, MFG-E8 may be a promising option for the treatment of pancreatic fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“…Through binding to integrin receptors, MFG-E8 exhibits versatile functions and is involved in a variety of cellular processes, such as maintenance and repair of intestinal epithelial cells, angiogenesis, and clearance of apoptotic cells (Kranich et al, 2010;Deng et al, 2017;Gao et al, 2018). Previous studies have indicated that MFG-E8 inhibited the activation of fibroblasts induced by TGF-β1, and recombinant MFG-E8 alleviated the development of fibrosis in the skin, heart, kidney and liver in mice (An et al, 2017;Fujiwara et al, 2019;Shi et al, 2020;Wang et al, 2020). Our recent study has shown that MFG-E8 restores mitochondrial function in acute pancreatitis (Ren et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial mesenchymal transition is a cellular transdifferentiation program, in which ECs partially lose their endothelial identity and acquire mesenchymal-like features and thus contribute to cardiac fibrosis ( Lovisa et al, 2020 ; Wang et al, 2020a ). The CD31 and VE-cadherin are endothelial markers and α-SMA and vimentin are fibrosis markers ( Zheng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…ECs can obtain mesenchymal phenotypes and express typical markers of myofibroblastic differentiation, and downregulate the expression of EC markers through a recognized process of endothelial-mesenchymal transition (EndMT; Pardali et al, 2017 ; Lovisa et al, 2020 ). Of note, EndMT contributes significantly to myocardial fibrosis, and prevention of EndMT may be a promising therapeutic strategy for DCM ( Medici et al, 2011 ; Zhu et al, 2018 ; Wang et al, 2020a ). However, the mechanisms of EndMT are not fully understood and no treatment to prevent or reverse the underlying molecular changes exists at this time.…”
Section: Introductionmentioning
confidence: 99%
“…The process of heart remodeling during HF often involves the activation of several ECs and mesenchymal cell transition-related pathways. These pathways include the cell-cell junction reconstruction [38], increased nuclear factor-κB (NF-κB) transcription factor activity [39], activation of the transforming growth factor β (TGF-β)/fibroblast growth factor (FGF) axis coordinating the endothelial cell plasticity and smooth muscle cell migration motility [40], activation of the Smad2/3-Snail signaling pathway to increase EndMT protein expression [41], and the regulation of microRNA (miRNA) expression for a positive or negative mediation of HF progression [42]. Our results showed that hypertensive or ischemic HF significantly reduced the E-cadherin and VE-cadherin expression and increased vimentin and fibronectin expression in the human and rat HF endocardium.…”
Section: Discussionmentioning
confidence: 99%